Pericardiocentesis Complicated by Pneumopericardium - Özkartal, Tardu (JACC Case Rep, 2019)
This report presents the case of pneumopericardium with trapped air in the pericardial sac occurring after a pericardiocentesis, probably caused by air leakage secondary to a defect in the drainage system and/or accidental removal of the pericardial tube. This condition is very rare and should be considered in case of hemodynamic worsening despite complete evacuation of the pericardial effusion, since immediate recognition and treatment are crucial. (Level of Difficulty: Intermediate.)